Purification process of high-purity quartz sand
By employing calcination and water quenching, microwave flotation, and acid leaching and drying processes, combined with modified collectors, the problem of substandard high-purity quartz sand preparation technology has been solved, achieving efficient and environmentally friendly quartz sand purification to meet the needs of high-tech industries.
Patent Information
- Application Number
- CN202511513584.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-22
- Publication Date
- 2026-01-23
AI Technical Summary
my country's high-purity quartz sand preparation technology is substandard, making it impossible to achieve industrial-scale mass production. Furthermore, existing flotation methods using acid and alkali treatment are harmful to the environment, costly, and difficult to meet the needs of high-tech industries.
High-purity quartz sand was produced by employing a process of calcination and water quenching, microwave flotation, and acid leaching and drying. Chloride salts were mixed and calcined to promote the transformation of quartz crystal form and the separation of impurities. Modified collectors were used to enhance the flotation effect. The hydrophobicity of quartz was improved by forming a three-dimensional network structure through modified collectors. Combined with microwave-assisted flotation and acid leaching treatment, high-purity quartz sand was produced.
It achieves efficient and environmentally friendly improvement of quartz sand purity, reduces production costs, and meets the demand of high-tech industries for high-purity quartz sand.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of quartz sand, in particular to a purification process of high-purity quartz sand. BACKGROUND
[0002] High-purity quartz sand has become an indispensable raw material in the fields of semiconductors, new energy, optical fiber communication, aerospace, etc. due to its excellent physical and chemical properties such as high-temperature resistance, corrosion resistance, low thermal expansion, high insulation and high light transmission. With the continuous progress of science and technology, the demand for high-purity quartz sand in high-tech industries is growing, and the quality requirements are also increasing accordingly. However, at present, China mainly relies on imports of high-purity quartz sand, and domestic high-purity quartz sand cannot meet the demand of the domestic market. The formation of this situation is mainly due to two reasons: first, the quality of the quartz ore in China does not meet the standard, and no quartz ore deposit suitable for preparing high-purity quartz sand has been found, or due to the imperfect exploration technology of the raw ore, the purification potential of the raw ore cannot be accurately evaluated; second, the preparation technology of high-purity quartz sand in China does not meet the standard, and the quartz raw ore cannot be purified to the required grade, or due to the widespread use of high-cost treatment technologies such as acid washing and chlorination, it is difficult to realize industrialized mass production.
[0003] Flotation is one of the most important purification methods in the purification process of quartz sand, which can effectively separate quartz from impurities and gangue minerals. Therefore, the flotation process is indispensable in the preparation process of all high-purity quartz sand. The selection of flotation reagents is a key factor affecting the flotation effect, mainly including collectors, depressants, regulators and foaming agents, etc. In addition, with the development of green environmental protection as an important direction of industrial production, the use of acid and alkali not only has potential harm to the environment, but also increases the cost of acid and alkali treatment. Therefore, the development of green and environmentally friendly flotation methods has become one of the research hotspots in the field of mineral processing today. SUMMARY
[0004] The application aims to provide a purification process of high-purity quartz sand to solve the problems in the prior art.
[0005] To solve the above technical problems, the application provides the following technical scheme: a purification process of high-purity quartz sand, specifically comprising the following steps: (1) Calcination and water quenching: first, the quartz ore is washed clean with deionized water, and then crushed to 2-5 mm particles in a crusher. Then, 8-14% of the weight of the quartz ore is added to the mixture and mixed evenly. The mixture is placed in a muffle furnace and calcined at 600-1000℃ for 2-6 hours. After calcination, the material is immediately poured into distilled water at 16-22℃ for water quenching treatment, which lasts for 0.1-1 minute. Then, dry at 100-150℃ for 3-5 hours. Finally, grind and sieve the dried material to obtain quartz sand.
[0006] (2) Microwave flotation: quartz sand is placed in a flotation tank equipped with a microwave device, deionized water and modified collector are added, and after stirring uniformly, flotation is carried out. The floating foam is collected, filtered, and washed with deionized water for 3 times to obtain purified quartz sand.
[0007] (3) Acid leaching and drying: the purified quartz sand is transferred to a container, 5-7 times of mixed acid solution by weight of the purified quartz sand is added, and stirring is carried out at 50 rpm for 2-4 hours. The solid is collected after filtration, soaked in sodium carbonate aqueous solution for 20-40 minutes, and then washed with deionized water. Subsequently, drying is carried out at 100-150℃ for 3-5 hours to obtain high-purity quartz sand.
[0008] Further, the chloride salt used in step (1) is selected from any one of sodium chloride, ammonium chloride and calcium chloride.
[0009] Further, the screen mesh size used in the sieving process in step (1) is in the range of 40 to 220 mesh.
[0010] Further, the preparation method of the modified collector in step (2) is as follows: 6-12 parts of (2-aminoethyl) trimethylammonium chloride hydrochloride, 8-14 parts of pentaerythritol and 30-50 parts of ethanol are mixed uniformly, nitrogen is introduced, 35-65 parts of bisphenol F diglycidyl ether-ethanol solution is added dropwise at a rate of 3 mL / min under the conditions of 20-30℃ and 100 rpm stirring, and after reaction for 30-40 hours, the temperature is increased to 65-75℃, and the reaction is continued for 25-35 hours. Concentration is carried out under vacuum degree of -0.1 to -0.08 MPa for 1-2 hours to obtain the modified collector.
[0011] Further, the concentration of bisphenol F diglycidyl ether in the bisphenol F diglycidyl ether-ethanol solution is 20wt%.
[0012] Further, the flotation conditions in step (2) include: air charge amount is 0.5-1.5 m³ / min, microwave frequency is 1250-2150 MHz, stirring speed is 150-300 r / min, and flotation time is 3-9 min.
[0013] Further, in step (2), the weight of deionized water is 4-8 times of the weight of quartz sand, and the weight of modified collector is 0.1-1.5% of the weight of quartz sand.
[0014] Further, the mixed acid solution in step (3) is prepared by mixing 6wt% sulfuric acid, 2wt% hydrochloric acid and 10wt% oxalic acid in a volume ratio of 1:2:1.
[0015] Further, the sodium carbonate content of the sodium carbonate aqueous solution in step (3) is 10wt%.
[0016] Further, in step (3), the pH value of the washing solution after washing ranges from 6.5 to 7.5.
[0017] Compared with the prior art, the present application has the following beneficial effects: The present application uses quartz ore as raw material. First, the quartz is mixed with a chloride salt and then calcined. During the calcination process, the quartz undergoes a crystal transformation and its volume increases. At the same time, the impurities in the crystal are converted into gaseous or condensed chlorides, thereby realizing the separation or enrichment of components and achieving the effect of deep purification. Subsequently, water quenching is performed. During the water quenching process, the volume of the crystal suddenly decreases and the internal stress at the defect site of the crystal rapidly increases, which promotes the rupture of the crystal at the defect site. This exposes the impurities in the inclusions and fissures in the original quartz to the surface of the particles, facilitating subsequent impurity removal. Then, under the assistance of microwaves, the quartz is subjected to flotation using a modified collector. Under the action of the microwave field, the lattice structure on the surface of the quartz sand will vibrate and adjust to a certain extent, which increases the difference in floatability between the quartz sand and the impurity minerals during the flotation process. At the same time, the molecular activity of the collector is enhanced, which promotes the chemical reaction between the collector and the surface of the quartz sand and the surface of the impurity minerals, thereby improving the purity of the quartz sand. Finally, acid leaching and drying treatment are performed to obtain high-purity multifunctional quartz sand.
[0018] The modified collector is prepared by copolymerization of (2-aminoethyl) trimethylammonium chloride hydrochloride, bisphenol F diglycidyl ether, and pentaerythritol. It forms a three-dimensional network structure. This structure can form multi-point adsorption with the active sites on the surface of the quartz, reducing the contact area between the quartz surface and water, thereby enhancing the hydrophobicity of the quartz and improving the separation effect. The quaternary ammonium salt structure introduced by (2-aminoethyl) trimethylammonium chloride hydrochloride is adsorbed on the surface of the quartz through electrostatic force, making the hydrophobic groups in the modified collector face the water phase, further enhancing the hydrophobicity of the quartz sand surface. This property makes the quartz sand more easily adhere to the gas bubbles and float with them, achieving the separation of quartz and impurity minerals. The multiple rigid benzene rings in bisphenol F diglycidyl ether can prevent water molecules from approaching the surface of the quartz, greatly improving the degree of hydrophobicity and facilitating the better adhesion of the quartz to the gas bubbles during the flotation process. At the same time, this structure also improves the stability of the collector under microwaves, indirectly enhancing its collecting ability. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0020] In order to more clearly illustrate the method provided by the present application, the following examples are used to illustrate the method in detail. In the following examples, the test methods for each index of the high-purity quartz sand prepared are as follows: Determination of SiO2 content and impurity element content: Take the same weight of the sample of the example and the comparative example, and analyze the content of each element in the quartz sand by inductively coupled plasma atomic emission spectrometry (ICP-OES) according to the standard JC / T2027.
[0021] Example 1: (1) Calcination and water quenching: Wash the quartz ore with deionized water, crush it to 2 mm particles in a crusher, and then add 8% sodium chloride based on the weight of the quartz ore and mix well. Place the mixture in a muffle furnace and calcine at 600°C for 2 h, then immediately pour into 16°C distilled water for water quenching for 0.1 min. Finally, dry at 100°C for 3 h, sieve after grinding with a 40 mesh sieve, and prepare the quartz sand.
[0022] (2) Preparation of modified collector: Mix 6 parts of (2-aminoethyl) trimethylammonium chloride hydrochloride, 8 parts of pentaerythritol, and 30 parts of ethanol uniformly. Bubble nitrogen gas, and under the condition of 20°C and 100 rpm stirring, add 35 parts of bisphenol F diglycidyl ether-ethanol solution with a concentration of 20wt% at a rate of 3mL / min. After 30 hours of reaction, heat to 65°C and continue to react for 25 hours. Finally, concentrate under a vacuum degree of -0.1 MPa for 1 hour to prepare the modified collector.
[0023] (3) Microwave flotation: Place the quartz sand in a flotation tank equipped with a microwave device, add 4 times the weight of deionized water based on the weight of the quartz sand, and 0.1% of the modified collector based on the weight of the quartz sand. After stirring uniformly, float for 3 minutes under the conditions of air supply amount of 0.5 m³ / min, microwave frequency of 1250 MHz, and stirring speed of 150 r / min. Collect the floating foam, filter the solid, and wash it with deionized water for 3 times to finally prepare the purified quartz sand.
[0024] (4) Acid leaching and drying: Transfer the purified quartz sand to a container, and add a mixed acid solution 5 times the weight of the purified quartz sand. The volume ratio of the mixed acid solution is 6% sulfuric acid: 2% hydrochloric acid: 10% oxalic acid = 1:2:1. Stir at 50 rpm for 2 h, filter the solid. Soak in a sodium carbonate aqueous solution with a sodium carbonate content of 10% for 20 min, wash with deionized water until the pH value of the washing liquid is 6.5, and then dry at 100°C for 3 h to prepare the high-purity quartz sand.
[0025] Example 2: (1) Calcination and water quenching: The quartz ore was washed clean with deionized water and crushed into 3.5 mm particles in a crusher. Then, 11% chloride salt by weight of the quartz ore was added, wherein the mass ratio of sodium chloride, ammonium chloride and calcium chloride was 1:3:0.5. The mixture was placed in a muffle furnace and calcined at 800°C for 4 hours, and immediately poured into distilled water at 19°C for 0.5 minutes for water quenching. Finally, it was dried at 125°C for 4 hours, ground and sieved through a 130-mesh sieve to obtain quartz sand.
[0026] (2) Preparation of modified collector: 9 parts of (2-aminoethyl)trimethylammonium chloride hydrochloride, 11 parts of pentaerythritol tetramine, and 40 parts of ethanol were mixed thoroughly. Nitrogen gas was introduced, and 50 parts of a 20wt% bisphenol F diglycidyl ether-ethanol solution were added dropwise at a rate of 3 mL / min under stirring at 25°C and 100 rpm. After reacting for 35 hours, the temperature was raised to 70°C, and the reaction was continued for another 30 hours. Finally, the mixture was concentrated under a vacuum of -0.09 MPa for 1.5 hours to obtain the modified collector.
[0027] (3) Microwave flotation: Quartz sand was placed in a flotation tank equipped with a microwave device, and deionized water at 6 times the weight of the quartz sand and modified collector at 0.8% of the weight of the quartz sand were added. After stirring evenly, flotation was carried out for 6 minutes under the conditions of an aeration rate of 1.0 m³ / min, a microwave frequency of 1700 MHz, and a stirring speed of 225 r / min. The floating foam was then collected, the solid was filtered, and washed 3 times with deionized water to obtain purified quartz sand.
[0028] (4) Acid leaching and drying: Transfer the purified quartz sand to a container and add a mixed acid solution with a weight of 6 times that of the purified quartz sand. The mixed acid solution is composed of 6 wt% sulfuric acid, 2 wt% hydrochloric acid, and 10 wt% oxalic acid in a volume ratio of 1:2:1. Stir at 50 rpm for 3 hours, and filter to obtain the solid. Then soak in a sodium carbonate aqueous solution with a sodium carbonate content of 10 wt% for 30 minutes, and wash with deionized water until the pH of the washing solution is 7.0. Finally, dry at 125℃ for 4 hours to obtain high-purity quartz sand.
[0029] Example 3: (1) Calcination and water quenching: The quartz ore was washed clean with deionized water, placed in a crusher, and crushed into 5mm particles. Then, 14% of the weight of the quartz ore was added with chloride salt. The mass ratio of sodium chloride, ammonium chloride, and calcium chloride in the chloride salt was 1:2:0.7. The mixture was placed in a muffle furnace and calcined at 1000℃ for 6 hours. Immediately after quenching in distilled water at 22℃ for 1 minute, it was dried at 150℃ for 5 hours. After grinding, it was sieved through a 220-mesh sieve to obtain quartz sand.
[0030] (2) Preparation of modified collector: 12 parts of (2-aminoethyl) trimethylammonium chloride hydrochloride, 14 parts of pentaerythritol, and 50 parts of ethanol were mixed uniformly. Under the condition of nitrogen gas being blown in, 65 parts of bisphenol F diglycidyl ether-ethanol solution with a concentration of 20 wt% was added dropwise at a rate of 3 mL / min under stirring at 30 °C and 100 rpm. After 40 hours of reaction, the temperature was raised to 75 °C and the reaction was continued for 35 hours. Finally, concentration was carried out under vacuum at-0.08 MPa for 2 hours to obtain the modified collector.
[0031] (3) Microwave flotation: The quartz sand was placed in a flotation tank with a microwave device, 8 times the weight of deionized water and 1.5% of the weight of the modified collector were added, and after stirring uniformly, the flotation was carried out under the conditions of air supply amount of 1.5 m³ / min, microwave frequency of 2150 MHz, and stirring speed of 300 r / min for 9 minutes. Subsequently, the floating foam was collected, the solid was filtered, and washed with deionized water for 3 times to obtain the purified quartz sand.
[0032] (4) Acid leaching and drying: The purified quartz sand was transferred to a container, and a mixed acid solution with a weight of 7 times that of the purified quartz sand was added. The mixed acid solution was prepared by mixing 6 wt% sulfuric acid, 2 wt% hydrochloric acid, and 10 wt% oxalic acid in a volume ratio of 1:2:1. After stirring at a speed of 50 rpm for 4 hours, the solid was filtered. The solid was soaked in a sodium carbonate aqueous solution with a sodium carbonate content of 10 wt% for 40 minutes, and then washed with deionized water until the pH value of the washing liquid was 7.5. Finally, the high-purity quartz sand was obtained by drying at 150 °C for 5 hours.
[0033] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that ammonium chloride is not added during calcination, and the remaining steps are the same as Example 2.
[0034] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the temperature is lowered to 100 °C after calcination and then poured into distilled water for water quenching, and the remaining steps are the same as Example 2.
[0035] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that no microwave is used during flotation, and the remaining steps are the same as Example 2.
[0036] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that (2-aminoethyl) trimethylammonium chloride hydrochloride is not added when synthesizing the modified collector, and the remaining steps are the same as Example 2.
[0037] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that bisphenol F glycidyl ether is not added when synthesizing the modified collector, and the remaining steps are the same as Example 2.
[0038] Comparative Example 6: Comparative Example 6 differs from Example 2 in that pentaerythritolamine is not added when synthesizing the modified collector, and the remaining steps are the same as those of Example 2.
[0039] Effect Example The performance analysis results of the high-purity quartz sand using Examples 1 to 3 and Comparative Examples 1 to 6 of the present application are given in Table 1 below.
[0040] Table 1
[0041] It can be found from the experimental data of Comparative Examples 1, 2, 3 and Comparative Examples 1, 2 that, by using the process of mixing and calcining with a chlorine salt first and then water quenching, the calcination process promotes the crystal type transformation of quartz and is accompanied by volume expansion, and at the same time, the impurity components in the crystal are converted into gaseous or condensed chlorides, thereby realizing the separation and enrichment of components and achieving the effect of deep purification. In the water quenching process, the volume of the crystal shrinks sharply, causing the internal stress at the defect of the crystal to increase rapidly, promoting the crystal to break at the defect, exposing the impurities in the inclusions and fissures in the original quartz to the surface of the particles, and facilitating the subsequent impurity removal treatment. In addition, it can be found from the experimental data of Comparative Examples 1, 2, 3 and Comparative Example 3 that, under the action of a microwave field, the lattice structure on the surface of the quartz sand will vibrate and adjust to a certain extent, which not only increases the difference in floatability between the quartz sand and the impurity minerals in the flotation process, but also enhances the molecular activity of the collector, promoting the chemical reaction between the reagent and the surface of the quartz sand and the impurity minerals, thereby further improving the purity of the quartz sand. It can be found from the experimental data of Comparative Examples 1, 2, 3 and Comparative Examples 4, 5, 6 that the modified collector prepared by copolymerization of (2-aminoethyl) trimethylammonium chloride hydrochloride, bisphenol F diglycidyl ether and pentaerythritolamine has the following characteristics: First, the collector can form a three-dimensional network structure and form multi-point adsorption with the active sites on the surface of quartz, thereby reducing the contact area between the surface of quartz and water and enhancing the hydrophobicity of quartz. Second, the introduced quaternary ammonium salt structure is adsorbed on the surface of quartz through electrostatic force, making the hydrophobic groups in the modified collector face the water phase, further enhancing the hydrophobicity of the surface of the quartz sand, making it easier to adhere to the gas bubbles and float with the gas bubbles, and realizing the separation of quartz and impurity minerals. In addition, the multiple rigid benzene rings in the collector can prevent water molecules from approaching the surface of quartz, significantly improving the degree of hydrophobicity, and making the quartz better adhere to the gas bubbles in the flotation process. On this basis, the stability of the collector under microwaves is also improved, thereby enhancing its collecting ability.
[0042] It will be apparent to those skilled in the art that the application is not limited to the details of the above-exemplified embodiments and that the present application can be implemented in other particular forms without departing from the spirit or essential characteristics of the present application. The embodiments should therefore be considered in all respects as illustrative and not restrictive, the scope of the application being indicated by the appended claims rather than by the above description, and all changes which come within the meaning and range of equivalency of the claims are therefore intended to be embraced therein. No reference herein to any prior art is to be taken as an admission that the present application is not entitled to antedate such prior art by virtue of prior application. Any reference to the term "comprising" is to be construed in accordance with the definition of that term provided in the preamble to Article 69 of the European Patent Convention. Any reference to the term "comprising" is to be construed in accordance with the definition of that term provided in the preamble to Article 69 of the European Patent Convention.
Claims
1. A purification process of high purity quartz sand, characterized by, The method comprises the following steps: (1) Calcination and water quenching: first, the quartz ore is cleaned with deionized water, and then crushed to 2-5 mm particles in a crusher. Then, 8-14% of the weight of the quartz ore is added to the mixture and mixed evenly. The mixture is placed in a muffle furnace and calcined at 600-1000°C for 2-6 hours. After calcination, the material is immediately poured into distilled water at 16-22°C for water quenching treatment for 0.1-1 minute. Then, it is dried at 100-150°C for 3-5 hours. Finally, the dried material is ground and sieved to obtain quartz sand; (2) Microwave flotation: the quartz sand is placed in a flotation tank equipped with a microwave device, deionized water and modified collector are added, and after stirring evenly, flotation is carried out. The floating foam is collected, filtered and washed with deionized water for 3 times to obtain purified quartz sand; (3) Acid leaching and drying: the purified quartz sand is transferred to a container, 5-7 times the weight of the purified quartz sand of mixed acid solution is added, and stirred at 50 rpm for 2-4 hours. After filtration, the solid is obtained, soaked in sodium carbonate aqueous solution for 20-40 minutes, and washed with deionized water. Then, it is dried at 100-150°C for 3-5 hours to obtain high-purity quartz sand.
2. The purification process of high purity quartz sand according to claim 1, characterized in that, The chloride salt used in step (1) is selected from any one of sodium chloride, ammonium chloride and calcium chloride.
3. The purification process of high purity quartz sand according to claim 1, characterized in that, The screen mesh size used in the sieving process in step (1) is 40 to 220 mesh.
4. The purification process of high purity quartz sand according to claim 1, characterized by, The preparation method of the modified collector in step (2) is as follows: 6-12 parts of (2-aminoethyl) trimethylammonium chloride hydrochloride, 8-14 parts of pentaerythritol and 30-50 parts of ethanol are mixed evenly, nitrogen is introduced, 35-65 parts of bisphenol F diglycidyl ether-ethanol solution is added dropwise at a rate of 3 mL / min under the conditions of 20-30°C and 100 rpm stirring, and the reaction is carried out for 30-40 hours. Then, the temperature is raised to 65-75°C, and the reaction is continued for 25-35 hours. Finally, it is concentrated under vacuum at-0.1~-0.08 MPa for 1-2 hours to obtain the modified collector.
5. The purification process of high purity quartz sand according to claim 4, characterized by, The concentration of bisphenol F diglycidyl ether in the bisphenol F diglycidyl ether-ethanol solution is 20wt%.
6. The purification process of high purity quartz sand according to claim 1, characterized by, The flotation conditions in step (2) include: air charge of 0.5-1.5 m³ / min, microwave frequency of 1250-2150 MHz, stirring speed of 150-300 r / min, and flotation time of 3-9 min.
7. The purification process of high purity quartz sand according to claim 1, characterized in that, In step (2), the weight of deionized water is 4-8 times the weight of quartz sand, and the weight of modified collector is 0.1-1.5% of the weight of quartz sand.
8. The purification process of high purity quartz sand according to claim 1, characterized by, The mixed acid solution in step (3) is prepared by mixing 6wt% sulfuric acid, 2wt% hydrochloric acid and 10wt% oxalic acid in a volume ratio of 1:2:
1.
9. The high purity quartz sand purification process of claim 1, wherein: The sodium carbonate content of the sodium carbonate aqueous solution in step (3) is 10wt%.
10. The high purity quartz sand purification process of claim 1, wherein: In step (3), the pH value of the washing liquid after washing ranges from 6.5 to 7.5.